Peterson field guide to weather - Anderson, Jay, 1947-; Pasachoff, Jay M.; Day, John A. (Writer on weather) (Peterson field guide series., 2021)
"A field guide to the weather, including clouds, storm systems, and climate change. A resource for those intrigued by events in the sky--clouds, precipitation, storms, aurora, halos--and for those who follow daily weather events. Using a nontechnical approach, the authors describe the flow of energy and moisture through global and local landscapes and how they evolve into day-to-day weather. For those fascinated by the sky's colors and patterns, there are halos, rainbows, iridescent clouds, and other tapestries in the sky. For the cloud-watcher, common and unusual cloud forms are covered; for those entranced by storms, the guide includes severe thunderstorms, winter blizzards, hurricanes, hail, ice storms, and other challenges that the atmosphere inflicts. It even includes a chapter on weather in the atmospheres of the planets and the sun. More than 400 photographs illustrate visible weather, and diagrams explain the more challenging physical concepts. This book is designed for those who want to look up, marvel, and understand what they see."--